Native Bacillus spp. strains as sustainable alternative in the yield of corn forage - Rodríguez-Hernández, Martha Georgina; Gallegos-Robles, Miguel Ángel; Rodríguez-Sifuentes, Lucio; Fortis-Hernández, Manuel; Luna-Ortega, J. Guadalupe; González-Salas, Uriel (REVISTA TERRA LATINOAMERICANA, 2020)
The use of growth-promoting microorganisms has great benefits, which help to reduce the excessive use of fertilizers and pesticides used in agricultural production. The objectives were to isolate, characterize and evaluate in the field strains of the genus Bacillus spp., in the yield of forage corn. The study was conducted in the experimental field of the Faculty of Agriculture and Zootechnics of the Juarez University of the state of Durango in the Lagunera Region, located in northern Mexico, during 2018. Bacillus spp., strains were isolated and identified, from roots of Johnson grass (Sorghum halepense), corn (Zea mays) and sorghum (Sorghum bicolor), preselected according to the ability to fix nitrogen and characterized by sequencing of the 16S rDNA gene. Two strains of Bacillus amyloliquefaciens and three more of Bacillus subtilis were identified. Subsequently evaluated in the field during the spring-summer (S-S) and autumn-winter (A-W) cycles of the year 2018, in two corn hybrids (Galactic and AG 614). Inoculation with the strain Bacillus amyloliquefaciens favored a good result for the fresh weight of the plant, dry weight, stem diameter, number of ears per plant, fresh root weight and length of the root; while Bacillus subtilis, better in fresh root weight compared to the control. Regarding the leaf area and the percentage of crude protein, a significant difference was shown between the treatments, with results similar to chemical treatment. Finally, for root diameter, the most favorable result was presented in chemical treatment. The best results were found during the S-S cycle.